Effect of ionic strength on ligand exchange kinetics between a mononuclear ferric citrate complex and siderophore desferrioxamine B. (1st April 2015) - Ito, Hiroaki; Fujii, Manabu; Masago, Yoshifumi; Waite, T. David; Omura, Tatsuo
Abstract: The effect of ionic strength ( I ) on the ligand exchange reaction between a mononuclear ferric citrate complex and the siderophore, desferrioxamine B (DFB), was examined in the NaCl concentration range of 0.01–0.5 M, particularly focusing on the kinetics and mechanism of ligand exchange under environmentally relevant conditions. Overall ligand exchange rate constants were determined by spectrophotometrically measuring the time course of ferrioxamine B formation at a water temperature of 25 °C, pH 8.0, and citrate/Fe molar ratios of 500–5000. The overall ligand exchange rate decreased by 2–11-fold (depending on the citrate/Fe molar ratios) as I increased from approximately 0.01 to 0.5 M. In particular, a relatively large decrease was observed at lower I (<0.1 M). A ligand exchange model describing the effect of I on the ligand exchange rate via disjunctive and adjunctive pathways was developed by considering the pseudo-equilibration of ferric citrate complexes and subsequent ferrioxamine formation on the basis of the Eigen–Wilkins metal–ligand complexation theory. The model and experimental data consistently suggest that the adjunctive pathway (i.e., direct association of DFB with ferric mono- and di-citrate complexes following dissociation of citrate from the parent complexes) dominates in ferrioxamine formation under the experimental conditions used. The model also predicts that the higher rate of ligand exchange at lower I is associated with the decrease in the ferric dicitrate complex stability because of the relatively high electrical repulsion between ferric monocitrate and free citrate at lower I (note that the reactivity of ferric dicitrate with DFB is smaller than that for the monocitrate complex). Overall, the findings of this study contribute to the understanding of the potential effect of I on ligand exchange kinetics in natural waters and provide fundamental knowledge on iron transformation and bioavailability.